Antioxidant Supplementation: A Linchpin in Radiation-Induced Enteritis. (December 2017) - Anwar, Mumtaz; Ahmad, Shabeer; Akhtar, Reyhan; Mahmood, Akhtar; Mahmood, Safrun
Radiation enteritis is one of the most feared complications of abdominal and pelvic regions. Thus, radiation to abdominal or pelvic malignancies unavoidably injures the intestine. Because of rapid cell turnover, the intestine is highly sensitive to radiation injury, which is the limiting factor in the permissible dosage of irradiation. Bowel injuries such as fistulas, strictures, and chronic malabsorption are potentially life-threatening complications and have an impact on patient quality of life. The incidence of radiation enteritis is increasing because of the current trend of combined chemotherapy and radiation. The consequences of radiation damage to the intestine may result in considerable morbidity and even mortality. The observed effects of ionizing radiation are mediated mainly by oxygen-free radicals that are generated by its action on water and are involved in several steps of signal transduction cascade, leading to apoptosis. The oxyradicals also induce DNA strand breaks and protein oxidation. An important line of defense against free radical damage is the presence of antioxidants. Therefore, administration of antioxidants may ameliorate the radiation-induced damage to the intestine.